Policy Coordination Instrument-Operational Guidance Note. (Policy Papers; Policy Paper ;, 2021)
This note provides general guidance on the use of the Policy Coordination Instrument (PCI), a non-financing instrument designed for countries that are seeking to unlock financing from multiple sources and/or to demonstrate a commitment to a reform agenda. Since its establishment in 2017 as part of the Fund's work on the Global Financial Safety Net, the PCI has been used by several members. These early experiences helped establish and refine best practices, which are reflected in the operational guidance note. The note covers operational issues in a broad range of areas such as purpose, objectives, and eligibility, modalities, applicability of UFR-related and other relevant policies, design of a PCI-supported program, conditionality framework, review cycle, and a comparison with other instruments. The note is an aid to the implementation of the policy and its underlying principles. If there is any instance in which a provision of the guidance note or its implementation conflicts with Board policy, Board policy prevails.